2022
DOI: 10.1039/d2nr02527b
|View full text |Cite
|
Sign up to set email alerts
|

A review on TiO2−x-based materials for photocatalytic CO2 reduction

Abstract: Photocatalytic CO2 reduction technology has a broad prospect in dealing with the issues of energy shortages and global warming. As a widely studied material used in photocatalytic process, titanium dioxide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 141 publications
0
45
0
Order By: Relevance
“…Defects with different structures inevitably exist in semiconductor materials. 1,2 Recent studies demonstrated that defect engineering can effectively tune the microstructure of materials, making them suitable for multi-domain applications, especially in photocatalysis. [3][4][5][6] Among many defect structures, zero-dimensional point defects (atom vacancy) have a more sensitive effect on the microstructure of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Defects with different structures inevitably exist in semiconductor materials. 1,2 Recent studies demonstrated that defect engineering can effectively tune the microstructure of materials, making them suitable for multi-domain applications, especially in photocatalysis. [3][4][5][6] Among many defect structures, zero-dimensional point defects (atom vacancy) have a more sensitive effect on the microstructure of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the design and fabrication of cheap, stable photocatalysts with high activity and selectivity is the key to CO 2 reduction. 7–12…”
Section: Introductionmentioning
confidence: 99%
“…In particular, titania has drawn significant attention as a model system to provide general insight into the chemistry of oxide surfaces. [1][2][3][4] Titania is a versatile reducible oxide that is used in numerous catalytic applications, including water splitting, [5][6][7] alcohol oxidation, 8,9 CO2 reduction, [10][11][12] and ketonization. [13][14][15][16] While rutile is the lowest energy polymorph of titania, anatase is more stable in a nanoparticulate form due to the lower surface energies.…”
Section: Introductionmentioning
confidence: 99%